An Investigation of Group Supervision Process of "Individual Counseling Practice Course" - Melike KOÇYİĞİT (Anı Publishing, 2020)
The purpose of this research was to describe how the group supervision process was conducted within the scope of the practicum and to determine the effective and ineffective components of group supervision process through analyzing both the supervisors' and counselor candidates' experiences. In this case study, the participants involved 16 counselor cadidates and four supervisors. A semistructured interview form, online diaries, the supervision scale were used as data collection tools. The data collection process continued throughout the 14-week supervision process. The findings gathered through the content analysis revealed that group supervision was carried out in four stages: (a) the forming phase, (b) preparation for practice, (c) practice phase, and (d) termination. For each phase, the focus of supervision, the roles of counselor candidates and supervisors, the supervision techniques used, the evaluation process were defined.